2018
DOI: 10.1111/jvs.12638
|View full text |Cite
|
Sign up to set email alerts
|

Elephant‐mediated compositional changes in riparian canopy trees over more than two decades in northern Botswana

Abstract: Questions: How has the composition and diversity of canopy tree species in a riparian woodland changed over time? How are the compositional changes related to impact of elephants? Does the composition of juvenile plants indicate that the woodland retains the potential to recover its former composition? Location: Northern Botswana adjoining the Linyanti River. Methods: We assessed the species composition of the riparian woodland in 2007/2008 along belt transects, recording living and dead individuals in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
(66 reference statements)
0
4
1
Order By: Relevance
“…The vegetation changes observed were modest despite the long‐term exposure to high elephant browsing pressure. The relatively modest vegetation changes revealed here are highly different from previous studies done in the Chobe National Park riverfront, Botswana, where local elephant densities are extreme during the dry season because this is the only source of water in the region during the dry season (Rutina & Moe, 2014; Teren et al, 2018), but are in accordance with another study carried out further into the Chobe National Park (>50 km from the river) where there are small effects of elephants on the woodlands (Kalwij et al, 2010). Taken together, these and our results suggest that elephant might have a drastic impact in large ecosystems that have reached an equilibrium, but only close to water sources.…”
Section: Discussioncontrasting
confidence: 99%
“…The vegetation changes observed were modest despite the long‐term exposure to high elephant browsing pressure. The relatively modest vegetation changes revealed here are highly different from previous studies done in the Chobe National Park riverfront, Botswana, where local elephant densities are extreme during the dry season because this is the only source of water in the region during the dry season (Rutina & Moe, 2014; Teren et al, 2018), but are in accordance with another study carried out further into the Chobe National Park (>50 km from the river) where there are small effects of elephants on the woodlands (Kalwij et al, 2010). Taken together, these and our results suggest that elephant might have a drastic impact in large ecosystems that have reached an equilibrium, but only close to water sources.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results of 33% losses are in line with these studies, and support our first hypothesis that higher elephant densities lead to substantial loss of woody biomass and related C stocks. Apart from the direct impacts of elephants also other drivers such as fire, a selective browsing of nutrient‐rich trees (Teren et al, 2018) and the potential interactions of these drivers with elephants may have contributed to the losses of aboveground woody biomass (Pellegrini et al, 2017). In this study, we cannot decipher the contribution of each individual factor, but following Davies and Asner (2019) we consider the impact of elephants to be the dominant one.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing numbers of megaherbivores impact ecosystem functioning at different spatial and temporal scales (Dirzo et al, 2014; Fullman & Bunting, 2014; Hempson et al, 2017). Previous studies have often outlined effects on vegetation characteristics such as on aboveground biomass (Guldemond et al, 2017) including vegetation structure and composition (Cromsigt et al, 2018; O’Connor & Page, 2013; Teren et al, 2018). Those studies found that browsing megaherbivores typically exerts strong negative effects on woody aboveground biomass, for example, by increasing the mortality rates within tree and shrub populations, thus also reducing the amount of carbon stored in aboveground biomass (Smit & Putman, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…debarking) and mortality to this species from elephant browsing are common and have been recorded at various locations (e.g. Northern Botswana (12% and 13%, Teren, Owen‐Smith, & Erasmus, 2018), Mkhuze Game Reserve [5.3%, 3.2%, White & Goodman, 2010]). However, unlike other species (see below), no studies have reported complete extirpation, and significant regeneration from elephant damage has been recorded (e.g.…”
Section: Discussionmentioning
confidence: 99%